Curricular Treatment of Body Image, Self-esteem and Self-concept in Spain - Rodríguez, Antonio V. (2015)
Adolescence is a period of human development in which problems with the perception of body image, self-esteem and self-concept proliferate, while the child is studying for Secondary Education. This study analyses the curricular treatment given to body image, self-esteem and self-concept in different legislative elements in the region of Valencia (Spain), using a qualitative methodology, through the technique of non-interactive documentary analysis. The results of the analysis of relevant academic planning stage documents in this region showed a presence of these statements contained in both the national Education Law and the regional education Law. They specifically appear in some elements of curriculum subjects such as Physical Education, Citizenship Education, Mathematics, Biology and Geology, Natural Science and Music, although not all of them take on the same role, emphasizing in this sense Physical Education as a subject that focuses more both on working and developing these aspects. Within the latter, a  imbalance is shown in terms of prominence achieved in what is intended to learn (objectives) and its negligible representation in the tools proposed to achieve it (content) as well as how to evaluate it (evaluation criteria).